The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1991
DOI: 10.3168/jds.s0022-0302(91)78266-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Clostridium tyrobutyricum by Bacteriocin-Like Substances Produced by Lactic Acid Bacteria

Abstract: Lactic acid bacteria were selected for their inhibitory activity against Clostridium tyrobutyricum under conditions that eliminate the effects of lactic acid and hydrogen peroxide. Four strains were isolated belonging to the species Lactococcus lactis ssp. lactis. The sensitivity of the inhibitory substances to pronase and trypsine indicates that they are proteins or peptides different from nisin. Their resistance to phospholipase D indicates that they are also different from lactostrepcin. The inhibitory subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
1
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 20 publications
0
26
1
3
Order By: Relevance
“…Both of microbes in inoculants were previously reported that those had ability to produce antibacterial substances. In term, L. plantarum secretes bacteriocins substances (Thuault et al, 1991;Gollop et al, 2005;Valan-Arasu et al, 2013) and S. cerevisiae generates oxylipins (Strauss et al, 2005) that those affect Clostridia and fungi inhibition.…”
Section: Physicochemical Characteristic Of King Grass Silagementioning
confidence: 99%
“…Both of microbes in inoculants were previously reported that those had ability to produce antibacterial substances. In term, L. plantarum secretes bacteriocins substances (Thuault et al, 1991;Gollop et al, 2005;Valan-Arasu et al, 2013) and S. cerevisiae generates oxylipins (Strauss et al, 2005) that those affect Clostridia and fungi inhibition.…”
Section: Physicochemical Characteristic Of King Grass Silagementioning
confidence: 99%
“…wide range of Gram-positive bacteria [3,4]. In this respect, its potential use as an agent to prevent late blowing of cheese due to Clostridium tyrobutyricum has been proposed [4].…”
mentioning
confidence: 99%
“…In this respect, its potential use as an agent to prevent late blowing of cheese due to Clostridium tyrobutyricum has been proposed [4]. The structural gene of lacticin 481 has been sequenced together with two adjacent genes, believed to be involved in lacticin 481 biosynthesis [5][6][7].…”
mentioning
confidence: 99%
“…These values were repeatedly obtained with a standard deviation of 1 and are consistent with the masses of the molecular ion [MϩH] ϩ and the adduct ions [MϩNa] ϩ and [MϩK] ϩ of lacticin 481. To verify that these peaks were indeed due to lacticin 481, we compared the following two pairs of strains: L. lactis C2102 and C2109 (Table 1), both of which were obtained from the wild-type lacticin 481 producer L. lactis ADRIA85LO30 (20,28) and which differ by the presence (C2102) or the absence (C2109) of the lacticin 481 operon (5); and L. lactis IL-1403(pEB94) and IL1403(pBS-pIL253), which carry the lacticin 481 operon on a recombinant plasmid and only its vector portion, respectively (21) ( Table 1). The expected peak cluster appeared in the spectra for the two lacticin 481-producing strains but not in the spectra for their nonproducing counterparts (data not shown) ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Lacticin 481 is a 2,901-Da lantibiotic (Fig. 1B) produced by some L. lactis strains (Table 1) (18,19,20,28). When whole bacteria grown on a plate were analyzed by MALDI-TOF-MS, a peak cluster covering the expected m/z value (m/z is the mass/charge ratio, where z is usually 1) was observed in the spectra from three different wild-type strains that produce lacticin 481, strains ADRIA85LO30 ( Fig.…”
Section: Resultsmentioning
confidence: 99%